Expertise, Emotion and Specialization in the Development of Persistent Burglary. (21st February 2020) - Meenaghan, Amy; Nee, Claire; Van Gelder, Jean-Louis; Vernham, Zarah; Otte, Marco
Abstract: This article describes a qualitative analysis of interviews conducted among 70 experienced residential burglars regarding the reasons for getting involved in and maintaining criminal behaviour. Themes emerging reflected an interaction between skill-development and affect, which played a key role in the initiation and continuation of burglary-related behaviour. Early participation in burglary seemed to be strongly influenced by the desire for excitement. Over time this diminished and was replaced by habitual engagement in burglary. With respect to the actual commission of offences, automatic decision-making appeared to be characteristic of the entire decision-chain, from initial thoughts to the commission of the burglary. Implications of the interaction between affect, cognition and expertise on diversification, specialization and desistance from crime are discussed.